Psychometric evaluation of the Chinese body shape questionnaire short form for assessing eating disorder symptoms among university students - Gao, Zeng; Zhao, Jing; Liu, Xi; Wang, Haitao; Zhang, Miaoling; Yuan, Han (Frontiers in Public Health, 2025)
BackgroundBody shape concerns have emerged in eating disorders as a public health issue among adolescents worldwide. The psychometric properties of the Body Shape Questionnaire (BSQ) remain underexplored in Chinese university students with eating disorder symptoms. This study aims to evaluate the reliability and validity of the Chinese version of the BSQ in the context of eating disorder symptoms among Chinese university students.MethodsA stratified random sample of 858 Chinese university students (age, mean ± SD = 19.91 ± 1.18) participated in the study. The surveys comprised the BSQ and the EDE-QS to assess body shape concerns with eating disorder symptoms. Eating disorder symptoms were defined as scores equal to or greater than 15 on the EDE-QS.ResultsThe Chinese version of the BSQ demonstrated strong internal consistency (Cronbach’s α = 0.92) and robust construct validity. Confirmatory factor analysis supported the original single-factor structure with satisfactory fit indices (Average Variance Extracted = 0.58, Composite Reliability = 0.92, Kaiser-Meyer-Olkin = 0.92, Normed Fit Index = 0.92, Goodness of Fit Index = 0.91, Comparative Fit Index = 0.93, Root Mean Square Error of Approximation = 0.09, Standardized Root Mean Square Residual = 0.03, Tucker-Lewis Index = 0.96). The BSQ showed significant correlations with the EDE-QS (p < 0.01).ConclusionThe Chinese version of the BSQ demonstrates strong psychometric properties among university students with eating disorder symptoms, supporting its use as a reliable and valid assessment tool in the Chinese population.